AB1153 EVALUATION OF DIAGNOSTIC DISCREPANCY USING THE ASAS CRITERIA AND F-18 NAF PET/CT IN PATIENTS WITH SUSPECTED AS. (June 2019) - Son, Seung Min; Lee, Jung Sub; Goh, Tae Sik
Abstract : Background: The latest ASAS diagnostic criteria allow early diagnosis of ankylosing spondylitis by using MRI. Nuclear imaging techniques may detect increased bone turnover not only during inflammation, but probably also paralleling postinflammatory reparative changes at starting point of new bone formation. Objectives: We focus on diagnostic discrepancy to evaluate AS between fluorine-18 sodium fluoride (F-18 NaF) PET/CT and assessment of spondyloarthritis international society (ASAS) criteria in patients with chronic low back pain suspected ankylosing spondylitis Methods: Sixty-eight patients with chronic lower back back pain over 3 months and limited lumbar movement were included. Among them, 49 patients who fulfilled ASAS diagnostic criteria were included as AS groups and 19 others were controlled. For clinical assessment, ESR, CRP, BASDAI, and BASFI scores were measured. For imaging assessment, conventional radiography for sacroillitis and F-18 NaF PET/CT were performed. We defined AS-positive lesions on PET/CT as uptake of sacroiliac joint, syndesmophyte, enthesitis lesions and facet joint. Results: No significant differences were observed in the baseline demographic evaluation between two groups in terms of age, sex. follow-up period and clinical parameters including BASDAI, BASFI, ESR level. However, there were significant differences in terms of HLA-B27 positive value, CRP level and standard uptake value ratio (SUVR) of sacroiliac joint in patients fulfilled ASAS criteria. Conclusion: In diagnosing AS, F-18 NaF PET/CT showed 79.59% sensitivity, 84.21% specificity and 80.88% accuracy. This shows the diagnostic value of the F-18 NaF PET/CT, which can be a good alternative to the diagnosis of early ankylosing spondylitis, and can evaluate whole body lesions in a single session. Disclosure of Interests: None declared